The effects of TeamSTEPPS implementation by nurses on situation monitoring in hospital - Ahsan Ahsan; Imeldha Monitasari; Evi Harwiati Ningrum; Ike Nesdia Rahmawati; Linda Wieke Noviyanti; Kuswantoro Rusca Putra (PAGEPress Publications, 2023)
Introduction: Patient safety is a healthcare system, which minimizes the occurrence and impact of side effects. It also helps to facilitate full recovery in patients, and efforts to improve their safety require teamwork, such as situation monitoring by nurses. Therefore, this study aims to determine the effects of TeamSTEPPS implementation by nurses on situation monitoring in hospitals. Design and Methods: A quasi-experimental pre-post test design was used with a total of 56 nurses, which were selected using the purposive sampling technique. They were then shared equally into 2 groups, namely control and intervention groups. Results: The unpaired t-test result shows that the value of |t count| was lower than the t table (0.210 < 2.005), while the p-value was greater than α (0.835 > 0.050). This result indicates that implementing TeamSTEPPS by nurses have an insignificant effect on situation monitoring in the hospital. Conclusions: In conclusion, hospitals are advised to implement TeamSTEPPS regularly to improve teamwork, specifically in situation monitoring by nurses.